2002
DOI: 10.1080/0899022021000009161
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aging on the subjective magnitude of vibration

Abstract: Two groups of subjects were tested using the method of Absolute Magnitude Estimation (AME) to determine the effect of age on the subjective intensity of vibration delivered to the skin of the hand. The mean age of the younger group was 23.5 years and that of the older group was 68.6 years. Average thresholds in the older group were higher in both the Pacinian (P) and non-Pacinian channel (NP II). The subjective magnitude of vibration was substantially lower at all intensities in the older group. Individual res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
39
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 44 publications
8
39
2
Order By: Relevance
“…One of the major risk factors for falling in the elderly is decreased somatosensory function in the feet (Magnusson et al 1990a) which can be tested clinically by determining sensation from plantar cutaneous mechanoreceptors on the soles of the feet. Various reports have demonstrated that ageing decreases the function of the plantar mechanoreceptors (Cauna and Mannan 1958;Verrillo et al 2002). Accordingly, it has been found that clinical tests of plantar cutaneous sensation such as vibration perception and tactile sensitivity are aVected by ageing (Perry et al 2000).…”
Section: Introductionmentioning
confidence: 97%
“…One of the major risk factors for falling in the elderly is decreased somatosensory function in the feet (Magnusson et al 1990a) which can be tested clinically by determining sensation from plantar cutaneous mechanoreceptors on the soles of the feet. Various reports have demonstrated that ageing decreases the function of the plantar mechanoreceptors (Cauna and Mannan 1958;Verrillo et al 2002). Accordingly, it has been found that clinical tests of plantar cutaneous sensation such as vibration perception and tactile sensitivity are aVected by ageing (Perry et al 2000).…”
Section: Introductionmentioning
confidence: 97%
“…Verrillo et al [23] also identified breaks in the slopes of magnitude estimation curves, demonstrating a change in the rate of increase in sensation above the threshold of the NP II channel (determined with a 0.008 cm 2 contactor). This suggested that the activity of more than one psychophysical channel contributed to the slope found by magnitude estimation.…”
Section: Experiments 2: Equivalent Comfort Contoursmentioning
confidence: 99%
“…The rate of growth in sensation with increasing magnitude has been determined using Stevens' power law (Stevens [20]), which describes the relationship between the psychophysical magnitude, , and the physical magnitude, , of a stimulus: where k is a constant, and the exponent n describes the rate of change of sensation, , al. [23] to explain steeper slopes in older subjects than in younger subjects at 250 Hz:…”
Section: Experiments 2: Equivalent Comfort Contoursmentioning
confidence: 99%
“…The NPII channel responds to vibration at similar frequencies to the Pacinian channel (40 -400 Hz), but has lower sensitivity unless a small stimulus area is used (2,15). The mechanoreceptor for the NPII channel has not yet been identified neurophysiologically in humans, but may be similar in structure to Ruffini endings (39). The NPIII channel may have a lower threshold than other channels in the range 0.4 and 4 Hz and has Merkel discs as the mechanoreceptor.…”
mentioning
confidence: 97%